Physics Stack Exchange is a question and answer site for active researchers, academics and students of physics. It's 100% free.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

Consider two particles moving in the same direction on the same line, $A$ and $B$, with mass $m_A$ and $m_B$, respectively. They also have velocies $u_A$ and $u_B$. They collide. After the collision A and B have velocities $v_A$ and $v_B$.

I want to prove the equation for the Principle of Conservation of Momentum:


So I begin:

Force is the rate of change of momentum, so

$F=\dfrac{\Delta mv}{\Delta t}$, so

$Ft=\Delta mv$.

Since the impulse on a particle is its change in momentum,

$I=\Delta mv=\Delta p$.

So taking partice B:

$I_B=\Delta p_B=m_Bv_B-m_Bu_B$.

And now A:

$I_A=\Delta p_A=m_Av_A-m_Au_A$.

I feel as if I'm on the right track to proving the equation, but how can I go from here?

I apologise if this seems like a homework question and doesn't belong here.

share|cite|improve this question
You mean $u_A$, I think. – Emilio Pisanty Jul 3 '13 at 17:54
up vote 1 down vote accepted

The key component you're missing is Newton's Third Law. The impulse on a particle is $I=\Delta p=F\Delta t$. The interaction time is the same but the forces are equal in magnitude and opposite in direction for the two particles: $$F_A=-F_B\text{ so }I_A=-I_B.$$ With that all you need is some algebra.

share|cite|improve this answer

Suppose the collision between particles A and B lasts some time $\tau$, and during the collision the force between the particles is some complicated function of time, $F(t)$.

Consider particle A. The total impulse on it is the force times time, or more generally the integral of the force over the collision time:

$$ I_a = \int_0^\tau F_a(t)dt $$

And the change of momentum of particle A is just the impulse, $I_a$. Exactly the same applies to particle B, so:

$$ I_b = \int_0^\tau F_b(t)dt $$

But we know that action and reaction are equal and opposite, so $F_a = -F_b$, and therefore $I_a = -I_b$.

The total change of momentum is $I_a + I_b$, and since we've just shown that $I_a = -I_b$ the change is $-I_b + I_b = 0$. So the total change of momentum is zero i.e. momentum is conserved.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.